Aspects Related to the Accommodation Tourist Infrastructure and the Tourist Flow from the Danube Delta and its Surroundings - Changes and Opportunities - Ionica SOARE (Dunarea de Jos University of Galati, 2021)
The sudy focusses on the Danube Delta and its surroundings at the level of accommodation units and the tourist flow from the localities that belong to Tulcea and Constanta counties. (Romania). On the basis of processing and analysing the series of statistic data after 1990 the territorial situation of the number of accommodation units on localities and types of units is being watched as well as the tourist flow in order to identify tendencies, localities as areas of concentration, the stage achieved by the accommodation basis and tourist flow at the expense of some incentive factors in the last years. In interpreting the statistic data there are also brought forward in discussion, aspects related to the capitalization of the natural landscape, tourist resources, the policy of the authorities regarding the development of tourism in the Reservation of The Danube Delta Biosphere. This space represents a spcial destination, a tourist region important for Romania, a place for which the authorities must maintain the balance between socio-economic development, including tourism and the environment.